Potential biomarkers reflecting inflammation in patients with severe periodontitis: Fractalkine (CX3CL1) and its receptor (CX3CR1). (28th February 2021) - Balci, Nur; Cekici, Ali; Kurgan, Şivge; Sahinkaya, Selin; Serdar, Muhittin A.
Abstract: Objective: The aim of this study was to determine differences in GCF and serum levels of fractalkine/CX3CL1 and its receptor/ CX3CR1 between the patients with stage III/grade B periodontitis and periodontally healthy subjects. Background: Fractalkine (CX3CL1), the only member of CX3C chemokine family, is involved in the pathogenesis of several systemic inflammatory diseases' disorders including rheumatoid arthritis, cardiovascular diseases, tonsillitis, and diabetes mellitus. It has critical functions in inflammatory cell migration, adhesion, and proliferation. Methods: 20 stage III/grade B periodontitis (P) and 20 healthy individuals (control; C) were included in this clinical study (all never smokers and systemically healthy). Clinical periodontal parameters were measured. Serum and GCF levels of CX3CL1, CX3CR1, and IL‐1β were quantified by enzyme‐linked immunosorbent assay and reported as total amounts and concentration. Results: The GCF concentrations and also total amount of CX3CL1, CX3CR1, and IL‐1β were statistically significantly higher in the patients with periodontitis compared with control group ( P  < 0.05). CX3CL1, CX3CR1, and IL‐1β levels in the GCF were significantly and positively correlated with all the clinical periodontal parameters (PI, PPD, BOP, and CAL; P  < 0.01, P  < 0.05). There was a significant correlation between IL‐1β, CX3CL1, and CX3CR1 concentrations in the GCF (respectively; r  = 0.838 and r  = 0.874, P  < 0.01). Conclusion: Fractalkine and its receptor may play role in mechanisms through the regulation of inflammation or on the pathogenesis of periodontal disease.